A Role for Communities in Primary Prevention of Chronic Illness? Case Studies in Regional Australia. (August 2013) - Taylor, Judy; Braunack-Mayer, Annette; Cargo, Margaret; Larkins, Sarah; Preston, Robyn
In regional Australia "communities of place, " defined as bounded geographic locations with a local society, undertake community-wide primary prevention programs. In helping to prevent chronic illness, communities provide valuable resources to the health system. To understand the role of community–health sector partnerships for primary prevention and the community contextual factors that affect them, we studied eight partnerships. We used an embedded multiple case study design and collected data through interviews, nonparticipant observation, and document analysis. These data were analyzed using a typology of community–health sector partnerships and community interaction theory to frame the key community contextual factors that affected partnerships. The dominant factor affecting all partnerships was the presence of a collective commitment that communities brought to making the community a better place through developing health. We call this a communitarian approach. Additional research to investigate factors influencing a communitarian approach and the role it plays in partnerships is required.